Berczeli Anzelm Károlyhoz - Csanádi püspök (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1937)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek